PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN PARTISIPASI SISWA PADA MATA PELAJARAN PPKn DI KELAS XI TKJ2 SMKN NEGERI 3 GORONTALO TAHUN PELAJARAN 2020/2021 - Wa Numini Mini (Gorontalo State University, 2023)
To achieve PPKn learning objectives, strategies and models are needed in learning that can increase student participation and creativity. To increase student participation, researchers choose the project/activity-based Project-Based Learning model as the medium. The purpose of this study is to increase student participation and learning outcomes by applying the Project Based Learning learning model to PPKn class XI TKJ2 subjects of SMK Negeri 3 Gorontalo. This research was carried out 2 (two) cycles in 4 (four) stages, namely planning, action, observation and reflection. From the results of the study, it can be described that the observation of Student Participation from all indicators observed in the first cycle was 13 (65%). Cycle II is 19 (95%). The results of the Student Comprehension Test in the first cycle were 11 students who completed or 41%, while those who had not completed there were 16 students or 59%. In cycle II there were 25 students who completed (92.6%), while those who were not completed there were 2 students (7.4%). Thus, it can be concluded that the results of the evaluation of students' ability to understand the material have increased by 52%.